2019
DOI: 10.1007/s12519-019-00324-5
|View full text |Cite
|
Sign up to set email alerts
|

Human bocavirus in children hospitalized for acute respiratory tract infection in Rome

Abstract: Background The role of human bocavirus (HBoV) as a respiratory pathogen has not been fulfilled yet. We aimed to describe clinical and serological characteristics of children with HBoV hospitalized for acute respiratory tract infection and to evaluate whether differences occur between HBoV alone and in co-infection. Methods We retrospectively reviewed data from 60 children (median age of 6.2 months, range 0.6-70.9) hospitalized for acute respiratory symptoms, with HBoV detected from a respiratory sample, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
(39 reference statements)
11
36
1
Order By: Relevance
“…Although the urine pH level was not investigated in the coronavirus-infected animals, this may be worth of an investigation. The sex bias was also observed that coronavirus tended to infect males [56,57]. Our data suggested that males were at a higher risk to be infected by COVID-19 and to develop more severe symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…Although the urine pH level was not investigated in the coronavirus-infected animals, this may be worth of an investigation. The sex bias was also observed that coronavirus tended to infect males [56,57]. Our data suggested that males were at a higher risk to be infected by COVID-19 and to develop more severe symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…hBoV was mainly discovered as a coinfection in Swedish children with ALRI of unknown aetiology in 2005 (71-75). One study reported that hBoV was responsible for severe ALRI presentation in children (76), but others reported no differences (77,78). As for the coinfection of hBoV with other viruses, some studies have concluded that both hBoV-and RSV-infected patients had more severe presentations (79,80) than hBoV-infected patients, while other studies indicated that the clinical presentation of the coinfection with hBoV-and RSV did not differ from hBoV infection alone (77), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Although the urine pH level was not investigated in the coronavirus-infected animals, this may be worth of an investigation. The sex bias was also observed that coronavirus tended to infect males (Habib et al, 2019;Petrarca et al, 2019). Our data suggested that males were at a higher risk to be infected by COVID-19 and to develop more severe symptoms.…”
Section: Discussionsupporting
confidence: 65%